The Impact of Attitudes towards Healthcare Service Quality on Organisational Performance: Evidence from the Saudi Arabia - Alsharari, Yaser Salman; Aziz, Fadzil Shah; Taib, Che Azlan; Yusoff, Rushami Zien (Macrothink Institute, 2017)
This research aims to investigate the effect of attitudes towards healthcare service quality on organisational performance among Saudi Arabian hospitals. The sample size comprises of 154 hospitals randomly chosen from 259 government hospitals in Saudi Arabia. For data analysis, the Partial Least Squares (PLS) structural equation modeling was used. In addition, this study found a positive and significant association between attitudes towards healthcare service quality and organisational performance. Eventually, this study provides some limitations and suggestions for future researchers.